Th2 cytokines impair innate immune responses to rhinovirus in respiratory epithelial cells. Issue 8 (24th April 2015) - Contoli, M.; Ito, K.; Padovani, A.; Poletti, D.; Marku, B.; Edwards, M. R.; Stanciu, L. A.; Gnesini, G.; Pastore, A.; Spanevello, A.; Morelli, P.; Johnston, S. L.; et al.
Abstract Background Asthma and other Th2 inflammatory conditions have been associated with increased susceptibility to viral infections. The mechanisms by which Th2 cytokines can influence immune responses to infections are largely unknown. Methods We measured the effects of Th2 cytokines (IL‐4 and IL‐13) on bronchial epithelial cell innate immune antiviral responses by assessing interferon (IFN‐β and IFN‐λ1) induction following rhinovirus (RV)‐16 infection. We also investigated the modulatory effects of Th2 cytokines on Toll‐like receptor 3 (TLR3), interferon‐responsive factor 3 (IRF3) and nuclear factor (NF)‐kB, that is key molecules and transcription factors involved in the rhinovirus‐induced interferon production and inflammatory cascade. Pharmacological and redox modulation of these pathways was also assessed. Results Th2 cytokines impaired RV‐16‐induced interferon production, increased rhinovirus replication and impaired TLR3 expression in bronchial epithelial cells. These results were replicated in vivo: we found increased IL‐4 mRNA levels in nasal epithelial cells from nasal brushing of atopic rhinitis patients and a parallel reduction in TLR3 expression and increased RV‐16 replication compared to nonatopic subjects. Mechanistically, Th2 cytokines impaired RV‐16‐induced activation of IRF3, but had no effects on RV‐16‐induced NF‐kB activation in bronchial epithelial cell cultures. N‐acetylcysteine and phosphoinositide 3‐kinase (PI3K) inhibitor restored the inhibitory effects of Th2 cytokines over RV‐16‐induced activation of IRF3. Conclusions IL‐4 and IL‐13, through inhibition of TLR3 expression and signalling (IRF3), impair immune response to RV‐16 infection. These data suggest that Th2 conditions increase susceptibility to infections and identify pharmacological approaches with potential to restore impaired immune response in these conditions.